Bureaucracy in a Democratic State A Governance Perspective - K E N N E T H J . M E I E R , L A U R E N C E J . O â€™ T O O L E J R . (The Johns Hopkins University Press, 2006)
Can the imperatives of an administrative system be reconciled with the norms of democratic governance? Or is bureaucracy, with its expertise, insulation, and byzantine procedures, the enemy of popular control? These questions have been raised wherever administrative institutions have been a key element in a broader pattern of purportedly democratic rule. Deep suspicions have typically been aroused in situations in which anonymous bureaucrats and their managers make decisions that affect the outputs and outcomes of public policy. Bureaucrats themselves, on the other hand, have been known to treat political overseers with some suspicion, if not outright disdain and evasion. These tensions have not dissipated with the rise of more complex patterns of â€œgovernanceâ€ that encompass multiple organizations and stakeholders in networks to co-produce policy resultsâ€”a set of developments receiving particular attention recently in Western Europe and North America. Indeed, the challenges posed by such broadened notions of â€œbureaucracy,â€ loosely speaking, for democratic governance are even greater